Patient safety environment in a healthcare institution in the amazon region of Ecuador (Horizontes de Enfermería, 2025)
Patient safety is an important and crucial issue because a good diagnosis can improve health systems within each health facility at the local and national levels. The objective of this research was to evaluate the patient safety environment in a health institution in the Amazon region of Ecuador. The study is a quantitative, non-experimental, descriptive, observational, and cross-sectional cohort; a convenience sample was considered consisting of 124 health professionals, mainly nursing staff 59.6% and doctors 16.1%, who work in this establishment, the majority being women 72.2%. Among the results of the AHRQ questionnaire, it was observed that there is a tendency towards appreciation or positive score for the four dimensions evaluated, which indicates a potential for growth in these areas: teamwork 66.67%, supervisor-manager relationship 60.22%, communication 58.18% and frequency of reported events 69.76%; being the frequency of reported events the most notable in positive evaluation, in addition it is also mentioned that in the supervisor-manager relationship there is a negative score of 23.66%. It is concluded that in this facility, there is an excellent potential for development with a positive patient safety climate; however, it is suggested that the relationship between workers and process supervisors be strengthened to prevent it from becoming a weakness.
Keywords: Patient safety; teamwork; communication; manager relationship; reported events